The Influence of Employee Engagement to Support Corporate Sustainability at PT Wiza - Lestari, Siska; Christina Nawangsari, Lenny (Journal Research of Social Science, Economics, and Management, 2022)
The development of industrial manufacturing processes around the world has resulted in various environmental damage. Companies that carry out business activities in addition to generating profits must also assist in solving related social problems. The community is increasingly aware of the social and environmental impacts that require companies to try to overcome the phenomenon of environmental damage. In general, this study analyzes the influence of employee engagement to support corporate sustainability. This study aims to analyze the influence of talent management and leadership on corporate sustainability through employee engagement. The research sample was 141 people from a total population of 520 employees of PT Wiza. This study uses a quantitative analysis approach, data collection is done using a questionnaire. The data analysis method uses Partial Least Square (PLS) with software version 3.2.9. directly talent management has a significant positive effect on employee engagement, employee engagement has a significant positive effect on corporate sustainability, and talent management and leadership have no effect on corporate sustainability. indirectly employee engagement mediates talent management and leadership on corporate sustainability.